Impaired adhesion of induced pluripotent stem cell-derived cardiac progenitor cells (iPSC-CPCs) to isolated extracellular matrix from failing hearts. Issue 10 (October 2018) - McKown, Elizabeth N.; DeAguero, Joshua L.; Canan, Benjamin D.; Kilic, Ahmet; Zhu, Yiliang; Janssen, Paul M.L.; Delfín, Dawn A.
Abstract: We tested the hypothesis that induced pluripotent stem cell-derived cardiac progenitor cells (iPSC-CPCs) are less able to adhere to the extracellular matrix (ECM) derived from failing human hearts with dilated cardiomyopathy compared to nonfailing human heart ECM. We also hypothesized that morphological development, cell beating rates, and mRNA levels of Nkx2.5 and cardiac troponin T would be altered after culturing the iPSC-CPCs on the failing heart ECM under cardiomyocyte differentiation conditions. We used microscopy to distinguish between adhered and unadhered cells, and to determine morphological development and cell beating. We used qPCR to determine mRNA levels. iPSC-CPCs show a significantly reduced ability to adhere to the ECM of failing hearts and higher expression of Nkx2.5 mRNA. However, morphological development, cell beating rates, and cardiac troponin T levels were not significantly altered in the cells cultured on the failing heart ECM. Our study shows that the failing heart ECM from patients with dilated cardiomyopathy impairs initial iPSC-CPC adhesion and may have a modest effect on the ability of the cells to transdifferentiate into cardiomyocytes.